FUNDAMENTALS OF HISTORICAL-CULTURAL THEORY AND HISTORICAL-CRITICAL PEDAGOGY: CORRELATES WITH CHILDHOOD AND EDUCATION - Ferreira, Lainara Flaviane Schmidt de Góes; Barreto, Aline Ramessess; Werle, Gabrielle; Sousa, Joceli de Fátima Arruda (Literatura em Debate, 2025)
The present study aims to analyze the interrelation between Historical-Cultural Theory (HCT) and Historical-Critical Pedagogy (HCP), highlighting how these approaches can contribute to an emancipatory education capable of overcoming social fragmentation. The essay is structured into sections to encompass the necessary elements to highlight the contributions of these theories in understanding child development, enhancing pedagogical actions. The first section explores the foundations of HCT, emphasizing the social origin of psychological functions, the periodization of child development, and the interdependence between thought and language. The second section, within the framework of HCP, explores the specificity of the teaching role and the relevance of a teaching method focused on liberating education that seeks to integrate objective historical knowledge into the school environment. Grounded in historical-dialectical materialism, the investigation draws on the works of authors such as Vygotsky and Saviani, among others. The expected results include a deeper understanding of how social and cultural interactions influence children's cognitive development, thereby guiding teaching practice. The conclusion reaffirms that schools, by mediating knowledge, play a fundamental role in the critical formation of individuals, integrating the concepts of content, form, and audience to promote social transformation.